The viability of speech-in-noise audiometric screening using domestic audio equipment. - Culling JF; Zhao F; Stephens D (International Journal of Audiology, 2005)
Speech-in-noise audiometry has potential application as a low-cost, self-screening test for sensorineural hearing loss. To realize this potential, the influence of variations in audio equipment and listening environment need assessment. The present study assessed: 1) the frequency response and distortion produced by a wide range of commercially available audio equipment; 2) the effects of such variations upon test results with normally hearing subjects using a simple, open-set, word-identification test; 3) the effect of distortion on the speech reception threshold using digitally applied distortion; and 4) the reliability of the test in listening environments with different levels of reverberation. In addition, preliminary tests were conducted with elderly listeners. The results indicate that variations in equipment have negligible effects on speech-in-noise audiometry. The only factor that substantially elevated normally hearing listeners' thresholds was high levels of room reverberation when using loudspeaker presentation. Variations in equipment and environment thus present no significant obstacle to the development of a self-administered audiometric screening test based on speech in noise.